The Association Between Household Financial Burden and Patient Mobility and Their Impact on Loss to Follow-Up Among Multidrug-Resistant Tuberculosis Patients in Guizhou, China - Wang Y; Huang Z; Chen H; Yuan Y; McNeil EB; Lu X; Zhang A (Dove Medical Press, 2023)
Yun Wang,1 Zhongfeng Huang,2 Huijuan Chen,3 Ye Yuan,2 Edward B McNeil,4 Xiaolong Lu,5 Aihua Zhang1 1Key Laboratory of Environmental Pollution Monitoring and Disease Control, Ministry of Education, School of Public Health, Guizhou Medical University, Guiyang, Guizhou, People's Republic of China; 2Department of Tuberculosis, Guiyang Public Health Clinical Center, Guiyang, Guizhou, People's Republic of China; 3Department of Tuberculosis Prevention and Control, Guizhou Center for Disease Prevention and Control, Guiyang, Guizhou, People's Republic of China; 4Department of Infectious Diseases, School of Public Health and Primary Care, Chinese University of Hong Kong, Hong Kong, People's Republic of China; 5School of Medicine and Health Management, Guizhou Medical University, Guiyang, Guizhou, People's Republic of ChinaCorrespondence: Aihua Zhang, Key Laboratory of Environmental Pollution Monitoring and Disease Control, Ministry of Education, School of Public Health, Guizhou Medical University, Guiyang, Guizhou, People's Republic of China, Tel +86 851 88416187, Fax +86 851 88416187, Email 97349238@qq.comPurpose: We aimed to assess the household financial burden due to multidrug-resistant tuberculosis (MDR-TB) treatment and its predictors, examine its association with patient mobility, and test their impact on patient loss to follow-up (LTFU).Methods: A cross-sectional study combining follow-up data collection was conducted at the largest designated MDR-TB hospital in Guizhou. Data were collected from medical records and questionnaires. Household financial burden was measured by the incidence of 2 indicators: catastrophic total costs (CTC) and catastrophic health expenditure (CHE). Mobility was classified as mover or non-mover after the patient's address was verified twice. A multivariate logistic regression model was used to identify associations between variables. Model I and Model II were separated by CHE and CTC.Results: Out of 180 households, the incidence of CHE and CTC was 51.7% and 80.6%, respectively. Families with low income and patients who were primary income earners were significantly associated with catastrophic costs. 42.8% of patients were movers. Patients from households with CHE (ORadj=2.2, 95% CI: 1.1- 4.1) or with CTC (ORadj=2.6, 95% CI: 1.1- 6.3) were more likely to move. Finding a job against financial difficulty (58.4%) was the top reason for movers. 20.0% of patients experienced LTFU. Patients from households with catastrophic payments (CHE: ORadj=4.1, 95% CI 1.6- 10.5 in Model I; CTC: ORadj=4.8, 95% CI 1.0- 22.9 in Model II), patients who were movers (ORadj=6.1, 95% CI 2.5- 14.8 in Model I; ORadj=7.4, 95% CI 3.0- 18.7 in Model II) and primary income earners (ORadj=2.5, 95% CI: 1.0- 5.9 in Model I; ORadj=2.7, 95% CI 1.1- 6.6 in Model II) had an increased risk of LTFU.Conclusion: There is a significant association between household financial burden due to MDR-TB treatment and patient mobility in Guizhou. They impact patients' treatment adherence and cause LTFU. Being a primary breadwinner increases the risk for catastrophic household payments and LTFU.Keywords: household catastrophic costs, migration, loss to follow-up, Guizhou, MDR-TB